The Impact of Indirect Taxation on the Plantation Sector in Indonesia - Setyawan, Dhani (Journal of Social and Development Sciences, 2012)
This study attempts to analyze the impact of the indirect taxes levy on the plantation sector in Indonesia. The aim of this study is to investigate the assumptions that the disincentive fiscal policy could generate some trade offs against some other economic variables i.e. National GDP level, Domestic Prices, total Exports and Imports, Poverty Rates, Government Revenues and Government Consumption Expenditures. This study employs the inter-regional CGE model with bottom-up approach and applying the Indonesian Social Accounting Matrix. The empirical results showed that, overall the disincentive fiscal policy in the plantation sector could give positive impacts not only to the area of the production forest sector, but also to the increasing number of the natural forest area in Indonesia. However, the implementation of this policy has some trade offs against some other economic variables.